Activating the souls of the older adults: insights into the psychological well-being of older adults through social interactions in the Guangdong-Hong Kong-Macao Greater Bay Area - Zhu, Xianglei; Du, Qian; Li, Yufen; Zhu, Yucheng; Ge, Chengwei; Chen, Jiawen (Frontiers in Public Health, 2025)
Background/objectivesAddressing the challenges faced by the older adults in the Guangdong-Hong Kong-Macao Greater Bay Area (GHMGBA) in terms of mental health and enhancing their well-being is pivotal for achieving the goals of cultural integration and intercity connectivity.MethodsThis study, grounded in social exchange theory, conducted an analysis using survey data collected from 6,500 older adults individuals in the Greater Bay Area (GBA). By constructing regression models, the research explores the impact of social interaction on the mental health of older adults individuals in the GBA.ResultsThe findings reveal that any form of social interaction among the older adults in the GBA significantly improves their mental health. However, the promotional effects vary significantly across different regions. In comparison to Guangdong, the impact of social interaction on the mental health of older adults individuals is more pronounced in Macao and Hong Kong. Notably, there is no significant difference in the impact of older adults social interaction on mental health between Hong Kong and Macao. Furthermore, the study identifies that intergenerational support plays an intermediary role in the social interactions and mental health of older adults individuals in the GBA.ConclusionIn the GBA should strengthen support for the social interaction of the older adults, promote communication among family members, and increase opportunities for the older adults to engage in social interactions. Future aging policies in the GBA should actively encourage downward intergenerational support, and intensify the exchange of intergenerational support.